Inside Back Cover: Synergistic Fusion of Vertical Graphene Nanosheets and Carbon Nanotubes for High‐Performance Supercapacitor Electrodes (ChemSusChem 8/2014). Issue 8 (31st July 2014) - Seo, Dong Han; Yick, Samuel; Han, Zhao Jun; Fang, Jing Hua; Ostrikov, Kostya (Ken)
<x xml:space="preserve">Abstract</x> The Inside Back Cover shows the synergistic integration of highly porous micropatterns of vertically aligned graphenes and carbon nanotubes and their application for high‐performance supercapacitor electrodes. This is achieved by fusing the carbon nanotubes in the basal plane of the vertical graphenes, which was synthesized from natural precursors by using an environmentally benign plasma process. The high electrochemical activity of the edge plane is retained, and the relatively inactive basal planes are filled with highly conducting carbon nanotubes. This combination of interconnected nanostructures substantially enhances the supercapacitor performance, thus making hybrid multidimensional nanoarchitectures promising energy storage devices for the future. More details can be found in the Full Paper by Han et al. on page 2317 (DOI: 10.1002/cssc.201302045).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>